Understanding the initial career decisions of hospitality management graduates in sri lanka - Karunarathne, A.C.I.D. (University of Jaffna, 2016)
Hospitality and tourism encounters a thriving protagonist in the Sri Lankan economy for last few years and human resource development has been identified as a foremost prerequisite in the momentous expansion of the sector. There is currently a severe dearth of employees in the hotel sector in relation to catering the authorities' targets. Tertiary academic stakeholders are currently crossing the threshold to fulfil the essentials fabricating graduates in Hospitality and Tourism Management. Yet, very less number of bachelor holders are working in the hotel industry as a paradigm. Initial career decision is a deciding factor in order to recruit and retain desirable and devoted employee in today's competitive labor market. The study investigates the initial career decisions of hospitality management graduates of Sri Lanka. Sample was undertaken with most recent graduating cluster who are ready to start their career after the four years special bachelor degree in the field of Hospitality Management from the national universities of Sri Lanka. Graduates' career prospects were identified by means of variouse dimensions utilizing a structured questionnaire and graduates were asked to rate each. Many hospitality management graduates have inadequate knowledge and unrealistic perceptions of the working conditions in the industry upon the commencement. By discovering interests and prospects of the recruitment pool, employers will be able to gain competitive advantages and develop successful human resource strategies knowing what graduates looking for. Meantime, Territory academic stakeholders would cultivate sustaining protocols to produce graduates who are physically and mentally fit with the industry careers.
Keywords: Career decision; Graduates; Hospitality industry; Hotel